Effect of Mean Grain Size on the Small-Strain Dynamic Properties of Calcareous Sand - Liwei Wen (Advances in Civil Engineering)
Calcareous sand was selected as the prior material for island reclamation in many coastal regions. The mechanical properties of the granular materials are greatly affected by their grain size distribution conditions. The shear modulus and damping ratio are two important parameters for earthquake ground response analysis and liquefaction evaluation. A series of resonant column tests had been performed on calcareous sands with varying median grain diameter and uniform coefficient. The dependence of the shear modulus and damping ratio of the calcareous sand on grain size has been confirmed in this examination. The test results reveal that the shear modulus decreases with a rise in shear strain for calcareous sand samples at a given confining pressure and relative density. The maximum shear modulus tends to increase with confining pressure and relative density. On the maximum shear modulus and void ratio plane, the trend lines of the measured results shift toward up and right position with a rise in grain diameter. The measured results indicate that the influence of uniform coefficient on the maximum shear modulus is neglectable. A revised empirical equation based on the Hardin model had been proposed considering the influence of grain diameter to estimate the maximum shear modulus of calcareous sand. The predicted values show satisfactory agreement with the measured results. The results manifest that the effect of grading condition on small-strain dynamic properties of calcareous sands cannot be neglected for the evaluation of seismic safety for reclamation engineering sites.